Influencing factors and mechanisms on self-governed rural public open space quality: a conceptual social-ecological system (SES) framework - Xuerui Shi; Gabriel Hoh Teck Ling (Humanities & Social Sciences Communications)
Abstract Self-governed public open spaces (POSs) face challenges related to collective action dilemmas, specifically the Hardinian tragedy of the commons and underinvestment. Despite extensive research on social-ecological systems (SES) addressing human-environment issues, there has been no quantitative empirical investigation into the determinants of governance in rural POSs. This study, operationalizing McGinnis and Ostrom’s SES framework and incorporating collective action theories, identifies institutional-social-ecological factors affecting the quality of self-governed POSs in rural China. Questionnaires were distributed to 594 households in 198 villages in Taigu via random sampling. The study employed PLS-SEM and mediation models to identify 15 key SES factors, including 4 institutional factors, 7 social factors, and 4 ecological factors. These variables impact the perceived quality of POSs either directly or through mediation by incentive activities, collective investment, and self-organizing activities. Based on the research findings, the study proposes five policy implications for the self-governance of rural POSs in China. The study not only contributes to the development of an SES-based POS governance framework, but it also offers policy insights into the significance of SES factors and ways to incentivize collective action for effective self-governance of rural public open spaces in China.